Postscript: Some Final Thoughts on Grandmother Cells, Distributed Representations, and PDP Models of Cognition. - Bowers, Jeffrey S. (Psychological Review, 2010)
A response to two commentaries that appeared in this issue on pp. 298–290 and pp. 297–299, respectively. The commentaries focused on an article by the writer on grandmother cells. He contends that localist representations are required to solve some fundamental computational tasks in perception and memory.